Localizing Global Energy Norms: Agency and Modality in Nusa Penida's Bottom-Up Energy Transition - Dwi Ardhanariswari Sundrijo; Dian Khairiani; Saroj Kumar Aryal (WIMAYA, 2026)
This article examines how non-state actors orchestrate bottom-up localization of energy transition norms in Indonesia, using Nusa Penida as a case study. Drawing on Amitav Acharya's framework of norm localization, and applying qualitative secondary data analysis as research method, the study argues that bottom-up initiatives offer potential for effective norm adaptation by leveraging local modalities. The Nusa Penida Initiative (NPI), initiated by a network of non-state actors, demonstrates emerging success through cultural framing, systematic roadmap planning, and community-based financing. The findings underscore that effective localization depends critically on non-state agency, funding modality, and local adaptive capacity. The article concludes that centering local actors and leveraging endogenous modalities are essential for inclusive and sustainable energy transitions in peripheral regions.